Research Progress and Prospect of Chinese Tourists’ Environmental Responsibility Behavior in Recent Years - Chai, Wang (International Journal of Social Sciences and Public Administration, 2025)
Since the 18th National Congress of the Communist Party of China (CPC), the "five-in-one" strategy has been put forward to the national "14th Five-Year Plan" tourism development plan, which clearly emphasizes the need to promote the construction of ecological civilization and the high-quality development of tourism. As the main actors in tourism activities, tourists have become important participants and implementers of ecological civilization construction in tourist destinations, and their social behaviors in the process of tourism have received extensive attention. However, on the whole, the research on tourists’ environmental responsibility behavior still lags behind the needs of practical development, and few studies have been systematically sorted out and analyzed, which limits the innovation and development of relevant policies. In order to track the research trend of tourists’ responsible behavior, this paper systematically sorted out the relevant literature on domestic tourists’ environmental responsibility behavior in recent years, and sorted out and analyzed its conceptual connotation, structure and scale, as well as its influencing factors and theoretical perspectives. On this basis, this study clarifies the future research direction from the perspectives of various stakeholders in the tourism process, so as to provide countermeasures and suggestions for relevant government management departments, residents and tourists to manage and cultivate environmentally responsible behaviors, and promote the construction and high-quality development of ecological civilization in tourism destinations.